(untitled) (Raparin Journal of Humanities (RJH), 2024)
Love as an accepted value in the community is reflected in the importance of being together and conserving society and family, because of its importance, it is continually studied by researchers and sociologists, due to the sociologists focus on an important regard of society, which is the family, the family, like any of the important systems of society, has undergone changes due to changes in social life and the rise of technology and family, like each significant social system of society that has faced changes due to the development of social life and the emergence of technology, and the role and status of the family has been included in this changes, so family also faced change, and this has led sociologists to say that the changes that have affected family relations, especially the relationships between spouses, have gone towards materialism and fading, and love has not been far from it as a feeling, and therefore domestic violence in the family has currently increased and more common than ever before.